Potensi dan Keterbatasan Kriya Wayang Krucil Malangan - Ranang Agung Sugihartono (Ornamen, 2006)
This article is taken from the result of the research by the title â€œKriya Wayang Krucil di Dukuh Turus Desa Trenyang Kecamatan Sumberpucung Kab. Malangâ€, which mean for knowing the real condition of wayang krucil craft in Malang recently. So that for the next time it will be possible to develop the wayang krucil craft of Malangan by increasing the skill and the capability of their craftman. The type of research used here is Qualitative Descriptive. The subject is wayang krucil in Dukuh Turus Desa Trenyang Kec. Sumberpucung Kab. Malang. The sourches of the data are the numbers of wayang krucuil, some craftman, and some appreciators of traditional art form Universitas Negeri Malang (UM). The data is taken by the researcher by using interview and observation methods. After that, the researcher analyzing the data by Qualitative Descriptive Technique to the ornament and visual element of wayang krucil, and also the visual changes of them. In this article, you will know the exposition of the real condition of the instruments and the materials used by the craftman, which are very limited and simple, the capabilities of the craftman who need to be increased, the potential art characteristics (the visual element and ornamen) of wayang krucil is very interesting, and the changes of visual element the wayang krucil ensharped Malangan style which is different with other places in Indonesia, especially from Central Java. From the results of this reseach, it is hoped that there will be any attention from all of us. Perhaps we can give them some production equipments, skill training, experiments of technique in producing wayang krucil, or even by opening the nets of selling the production of wayang krucil.